Comparison of three techniques of nasogastric tube insertion in anaesthetised, paralyzed, and intubated patients: A rendomized open-labelled trial / Khaw Teik Seng - Khaw , Teik Seng (2017)
BACKGROUND: The insertion of nasogastric tube (NGT) in anaesthetized, paralyzed and intubated or unconscious patients may be difficult due to loss of swallow refle in these patients, with a reported failure rate or nearly 50% on the first attempt, with the head in neutral position. After a failure, subsequent attempts are usually unsuccessful due to coiling, kinking or knotting of the NGT as it Iosses stiffness due to warming to body temperature. The memory effect also contributes to subsequent failure: once kinked, the NGT is subsequently more like to kink at the same place. Common methods used to facilitate NGT insertion include the use of a slit endotracheal tube, uretheral guidewire as stylet, forward di placement of the larynx, head flexion, lateral neck pressure, head turning, direct laryngoscope with various forceps, use of gloved fingers to steer the NGT after impaction. In this study, we are comparing the success rate, average time of insertion, and incidence of complication between modified techniques (contralateral cricothyroid pressure and ipsilateral head turning) and conventional technique in NGT insertion. METHOD: Hospital Ethnic Committee approval was obtained and a valid written informed consent was obtained from each patient, who fulfilled inclusion criteria. This is a prospective, randomized and open-labelled trial. This power study was performed by using web bases sample size calculator. 81 patients enrolled into this study were randomly allocated into three groups (the conventional technique group, the contralateral cricoid pressure, and the ipsilateral head turning group ) according to a computerized, random-allocation software program (n=27 per group). The investigator will be responsible to judge whether the attempt was a success or a failure, and whether any complication has occurred. RESULTS: The modified techniques had a higher success rate and lower complications rates compared to conventional technique in NGT insertion in anaesthetized, paralyzed and intubated patients. The contralateral cricothyroid pressure had a highest success rate (66.6%), followed by ipsilateral head turning (63%), and the lowest rate was conventional technique (49.1 %). These sequence were similar in first attempt success in NGT insertion, 51.9% for contralateral cricothyroid pressure, 48.1% for ipsilateral head turning and 25.9% for conventional technique. The conventional technique had the highest overall complications rate (74.1 %) as well as the sub-complications [kinking (29.6%), coiling (48.1 %) and bleeding (48.1%)]. However, there were no significant association between success rate and complications with the three techniques, except bleeding complication was statiscally lower in the modified techniques 'compared to conventional technique in NGT insertion. CONCLUSION: With this present study, the modified techniques has shown to be better than conventional technique in terms of higher success rate and lesser complications in NGT insertion. Only bleeding complication was statistically lower in modified techniques comparing to conventional technique, otherwise there were no statistically significant association between the success rate and complications among the three techniques. However, we will still consider modified technique in NGT insertion in our clinical practice. The contralateral cricothyroid (CLCT) pressure will be the preferred method for NGT insertion in patients with cervical pathology and trauma patients on cervical collar.